INFLATION CONTROL IN ASIA: EMPIRICAL STUDY OF THE INFLUENCE OF DIGITAL TECHNOLOGY AND TRADE OPENNESS POST THE GLOBAL FINANCIAL CRISIS - Moch Zaka Amar M; Alvin Sugeng Prasetyo; Vinda Yulinda (Prodi Ilmu Hubungan Internasional, Universitas Fajar, 2024)
vindayulinda05@gmail.com Abstract - This study aims to test and analyze the role of trade openness in controlling inflation and to test and analyze the role of ICT indicators in controlling inflation after the global financial crisis in Asia. As well as to measure and analyze the inflation rate in developing Asian countries in moving towards the balance line (Asian inflation average). The variables of this study use CPI, trade, fixed broadband subscription, fixed telephone subscription, mobile cellular subscription, individuals using the internet, foreign direct investment, exchange rate, GDP, and unemployment. Time series data from 2010 to 2021 and cross-section data of 22 developing countries on the Asian continent. The method used is the General method moment (GMM), while the analysis technique is SYS-GMM. Results The estimation results indicated that Trade openness could decrease but not significantly. The SYS-GMM results of the four ICT indicators fixed broadband, fixed telephone, mobile cellular, and individuals using the internet have different effects on inflation. SYS-GMM results of the four ICT indicators fixed broadband, fixed telephone, mobile cellular, and individuals using the internet have a different effects on inflation. Only ICT 4 individuals using the internet can significantly reduce inflation in ASIA after the global financial crisis.